3(w-6)-5w=-36

Simple and best practice solution for 3(w-6)-5w=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(w-6)-5w=-36 equation:


Simplifying
3(w + -6) + -5w = -36

Reorder the terms:
3(-6 + w) + -5w = -36
(-6 * 3 + w * 3) + -5w = -36
(-18 + 3w) + -5w = -36

Combine like terms: 3w + -5w = -2w
-18 + -2w = -36

Solving
-18 + -2w = -36

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + -2w = -36 + 18

Combine like terms: -18 + 18 = 0
0 + -2w = -36 + 18
-2w = -36 + 18

Combine like terms: -36 + 18 = -18
-2w = -18

Divide each side by '-2'.
w = 9

Simplifying
w = 9

See similar equations:

| h=-5t^2+60t | | 7x+3x+90=180 | | -16t^2+24t+3=12 | | X^3-9x^2+20x-12=0 | | 3x(x-9)= | | 3+2t=13 | | 5x-2= | | 3x^3+3x^2-11x-10=0 | | 4.2(x-1)=9.8 | | (x)(x)(x)+4(x)(x)-25x-100=0 | | 25x-10= | | x^2+5x=x(x-11) | | -12=-7-3.5s | | 7xy+1xy=72 | | (x)(x)(x)+4(x)(x)-100=0 | | 6x+10= | | n=wsv | | 7(a+1)-3a=5+4(a-1) | | 2(x-7)=3 | | -18y=da | | 1.33x+2=-1 | | 1.33+2=-1 | | 2*-8.5+13.6=0.4*-8.5 | | 5(3-t)-(3-3t)=5 | | 8x^6+6x^3+7=0 | | 3x+11=25 | | r^2-15r+54=0 | | 4x+10y-8+4x-4y= | | x^2-x-110=0 | | 10-a+3a=6 | | 3n+8= | | 2*-8.5+13.6=0.5*-8.5 |

Equations solver categories